Iron ore : mineralogy, processing and environmental sustainability - Lu, Liming (Woodhead Publishing, 2021)
Iron Ore: Mineralogy, Processing and Environmental Sustainability, Second Edition covers all aspects surrounding the second most important commodity behind oil. As an essential input for the production of crude steel, iron ore feeds the world's largest trillion-dollar-a-year metal market and is the backbone of the global infrastructure. The book explores new ore types and the development of more efficient processes/technologies to minimize environmental footprints. This new edition includes all new case studies and technologies, along with new chapters on the chemical analysis of iron ore, thermal and dry beneficiation of iron ore, and discussions of alternative iron making technologies. In addition, information on recycling solid wastes and P-bearing slag generated in steel mills, sustainable mining, and low emission iron making technologies from regional perspectives, particularly Europe and Japan, are included. This work will be a valuable resource for anyone involved in the iron ore industry.
Keywords: Iron ores.; Iron mines and mining -- Environmental aspects.; elektronické knihy; electronic books